(untitled) (Revista Nacional de Odontología, 2023)
Timely treatment of maxillary expansion can be classified into different types depending on the time, the structure, the material and the location in which it is going to be placed. It can be implemented as a non surgical intervention method, considering the dental and bone age of the patient, in order to achieve notable changes, compared to the possibility of other invasive treatments in which the need for its use can be postponed or eliminated. There are different types of maxillary expanders and an infinity of orthopedic techniques and treatments that can be implemented, however, it is important to emphasize the diagnosis, use and choice of the correct orthopedic appliance for each patient. Therefore, dental retention is one of the most common reference reasons in the area of orthopedics and surgery and is recommended for the restoration of aesthetics and functional dental arches, depending on the retention and location of the dental organ. that may be affected by this pathology, an adequate bone and dental study must be carried out, knowing the eruption times and their possible delays due to factors not linked to genes or trauma. The clinical case of a 14-year-old patient with a retained temporary dental organ is presented without knowing the reason why the respective dental replacement did not occur. In the first instance, the patient received a minimally invasive surgical intervention to extract the piece and thus obtain the space and eruption route for the retained dental piece in the upper jaw, after the lack of clinical changes, the decision was made to perform an orthopedic treatment to support the eruption and provide more space in the arch, with a Hyrax type slow maxillary expansion device, with which it was possible to show changes in angulation and placement in the appropriate space for the exfoliation of the respective tooth. Allowing the choice of a cheaper treatment and with generalized changes both in the dental arch and in the masticatory function of the patient, who had been affected by her occlusion and unfavorable bone growth.